Digital Classroom:Survey and Contributions - Sheth, P. D. (Journal of Engineering Education Transformations, 2016)
India has very auspicious tradition of teaching learning from the ages. The ischolar_mains of Indian teaching learning system have been found in old Ashramas, then in middle age universities like Nalanda and now in world class institutes like the IITs. Over the ages teaching learning aids got changed and today's demand is Digital classroom. This paper highlights the profile of Digital Classroom. The modern technologies used in the digital classroom are also enlisted in this paper. At the end, paper describes three novel methods of teaching learning applied by the author. The new methods: Alpha Learning, Online Group Discussion and Debate Digital are well suited to the digital classroom environment. They boost student interest by making them learn through one of their preferred mediums.